2011
DOI: 10.1021/cb2000567
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Cofactor Repertoire of Protein Lysine Methyltransferase for Substrate Labeling

Abstract: Protein lysine methyltransferases (PKMTs) play crucial roles in normal physiology and disease processes. Profiling PKMT targets is an important but challenging task. With cancer-relevant G9a as a target, we have demonstrated the success in developing S-adenosyl-L-methionine (SAM) analogues, particularly (E)-hex-2-en-5-ynyl SAM (Hey-SAM), as cofactors for engineered G9a. Hey-SAM analogue in combination with G9a Y1154A mutant modifies the same set of substrates as their native counterparts with remarkable effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
182
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(190 citation statements)
references
References 36 publications
6
182
0
2
Order By: Relevance
“…37,38 Usually, the wild-type enzymes were tested for promiscuous activity on SAM analogs and directed evolution was limited to semi-rational approaches. 39 We also show how our setup can be readily implemented for screening of methyltransferase inhibitors. As a proof of concept, we tested three known methyltransferase inhibitors and found that only (-)-epigallocatechin gallate inhibited hTGS1.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Usually, the wild-type enzymes were tested for promiscuous activity on SAM analogs and directed evolution was limited to semi-rational approaches. 39 We also show how our setup can be readily implemented for screening of methyltransferase inhibitors. As a proof of concept, we tested three known methyltransferase inhibitors and found that only (-)-epigallocatechin gallate inhibited hTGS1.…”
Section: Resultsmentioning
confidence: 99%
“…After processing the reaction at ambient temperature (22°C) for specific time intervals, the peptide sample was enriched by C18 ZipTip (Millipore), washed with 0.1% TFA/ddH 2 O (vol/vol) 10 times, and eluted out with 50% acetonitrile/0.1% TFA, according to the manufacturer's instructions. The resultant peptide products were subjected to MALDI-MS as described previously (42). Briefly, to prepare MALDI-TOF-MS samples, 2 μL of the purified peptide was mixed with 1 μL of saturated α-cyano-hydroxy-cinnamic acid solution (50% acetonitrile/0.1% TFA) on a MALDI sample plate and allowed to dry at ambient temperature (22°C).…”
Section: Methodsmentioning
confidence: 99%
“…The biological relevance of SET8, as well as our general interest in PKMTs, inspired us to leverage BIE and KIE studies of SET8 to explore bond motions along the reaction path of the PKMT-catalyzed methylation. Given the convenience of MS in characterizing protein methylation (42,43), we developed a matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS) method and corresponding mathematic matrix to determine precisely the ratios of isotopically labeled H4K20 peptide. With this approach, BIEs and KIEs of SAM and SeAM (Se-adenosyl-L-selenomethionine, a more reactive SAM surrogate) were determined for SET8-catalzyed H4K20 methylation.…”
Section: Significancementioning
confidence: 99%
“…For example, incorporation of different transferrable amine moieties ( 21 ,4, 18 22 ,4, 19 23 ,4, 19b Table S2) can be followed by a coupling reaction with the N ‐hydroxysuccinimide (NHS) ester of an amine‐reactive probe 18. In addition, several examples exist on the application of AdoMet analogues with a transferrable terminal alkyne ( 5 ,20 Scheme 6; 20 ,20g,20h 24 ,20b,20c,20g and 25 ,4, 19b Table S2) or azide ( 26 g ,20, 21 27 ) 4. The transferred alkynes and azides can be further functionalized by using the biocompatible and highly‐efficient azide–alkyne cycloaddition reaction (one of the “click” series of reactions).…”
Section: Labeling Strategies Using Adomet‐dependent Mtasesmentioning
confidence: 99%
“…The focus of their work has been the human protein MTases G9a (also known as EuHMT2), GLP1 (also known as EuHMT1), and PRMT1 (for a complete overview, see Table 2). Enzyme‐mediated transalkylation reactions using an azido‐modified AdoMet analogue with engineered G9a and GLP121, 60 and an alkyne‐modified AdoMet analogue with engineered G9a20c and PRMT1 have been demonstrated 20g. Additionally, a selenium‐based SAM analogue with an alkyne linker was effectively employed in transalkyation reactions directed and catalyzed by the native protein MTases GLP1, G9a and SUV39H2 28, 60, 61…”
Section: Labeling Strategies Using Adomet‐dependent Mtasesmentioning
confidence: 99%